The Impact of Social Media Use (TikTok/Instagram) on Generation Z's Understanding and Practice of Worship: An Islamic Religious Education Perspective - Muhammad Suma Hafiz; Neni Neni (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
The study aims to comprehensively analyze and synthesize the impact of two dominant social media platforms, TikTok and Instagram, on two fundamental aspects of Generation Z's (Gen Z) religiosity: understanding of Islamic teachings and practice of worship, viewed from the perspective of Islamic Religious Education (PAI). Gen Z, as true digital natives, exhibits a massive reliance on online content, which fundamentally transforms how they access and internalize religious values. This shift creates serious challenges related to Digital Religious Literacy, where Gen Z's understanding of worship tends to be fragmentary and susceptible to algorithmic bias. In practice, worship is often shifted from the spiritual-personal domain to the public-social domain, increasing the risk of digital riyā' (showing off) and eroding khushū'(solemnity) due to digital distractions. The research method employed is a qualitative library research (study of literature). Data were systematically collected through documentation techniques from various primary and secondary sources, including reputable scientific journals, reference books, and recent studies on digital literacy, adolescent psychology, and Islamic education. The collected data were then analyzed using content analysis to identify patterns, value shifts, and formulate an PAI-based solution framework. The findings highlight a crisis of spiritual integrity and authenticity in worship among Gen Z. In response, the study posits the strategic role of PAI as a critical intervention.